What the river knows ebook A novel. - Ibañez, Isabel (Secrets of the Nile, 2023)
The Mummy meets Death on the Nile in What the River Knows , Isabel Ibañez's lush, immersive historical fantasy set in Egypt and filled with adventure, a rivals-to-lovers romance, and a dangerous race. Bolivian-Argentinian Inez Olivera belongs to the glittering upper society of nineteenth century Buenos Aires, and like the rest of the world, the town is steeped in old world magic that's been largely left behind or forgotten. Inez has everything a girl might want, except for the one thing she yearns the most: her globetrotting parents—who frequently leave her behind. When she receives word of their tragic deaths, Inez inherits their massive fortune and a mysterious guardian, an archeologist in partnership with his Egyptian brother-in-law. Yearning for answers, Inez sails to Cairo, bringing her sketch pads and a golden ring her father sent to her for safekeeping before he died. But upon her arrival, the old world magic tethered to the ring pulls her down a path where she soon discovers there's more to her parent's disappearance than what her guardian led her to believe. With her guardian's infuriatingly handsome assistant thwarting her at every turn, Inez must rely on ancient magic to uncover the truth about her parent's disappearance—or risk becoming a pawn in a larger game that will kill her. What the River Knows is the first book in the thrilling Secrets of the Nile duology. "Expertly plotted, explosively adventurous, and burning with romance." - Stephanie Garber #1 New York Times bestselling author "Take a plucky heroine, a historically grounded Indiana Jones-esque adventure through Ancient Egypt, and add a surprising dollop of magic — it's a recipe for a delightful read." - Jodi Picoult, #1 New York Times bestselling author *Book 1 in the Secrets of the Nile duology*